2020
DOI: 10.17576/jkmjc-2020-3603-21
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of eWOM Credibility on the Online Purchasing Activities among Consumers Through Social Media

Abstract: Word of mouth (WOM) communication has become a thoughtful information-sharing medium which can affect consumers' buying decisions and attitudes in the direction of product categorizations and brands. Conventional word of mouth (WOM) is an outdated method for sharing thoughts and has existed as far back as individuals traded data which now evolved to the new form of word of mouth which is the electronic word of mouth (eWOM). This study attempts to analyse the dimensions of eWOM credibility on online purchasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…If the reviewer agrees with most of online reviews or recommendations of others those reviews are considered as consistent reviews (Chakraborty andBhat 2017, 2018b;Chakraborty 2019). The consistent online reviews were found to have higher credibility (Abedin et al 2021;Baharuddin and Yaacob 2020;Brand and Reith 2022;Chakraborty andBhat 2017, 2018b;Chakraborty 2019;Cheung et al 2009Luo et al 2014;Tran and Can 2020). Fang and Li (2016) found out that receiver of the information actively monitors the consistency of the information while perceiving the credibility of review.…”
Section: Review Characteristicsmentioning
confidence: 97%
See 1 more Smart Citation
“…If the reviewer agrees with most of online reviews or recommendations of others those reviews are considered as consistent reviews (Chakraborty andBhat 2017, 2018b;Chakraborty 2019). The consistent online reviews were found to have higher credibility (Abedin et al 2021;Baharuddin and Yaacob 2020;Brand and Reith 2022;Chakraborty andBhat 2017, 2018b;Chakraborty 2019;Cheung et al 2009Luo et al 2014;Tran and Can 2020). Fang and Li (2016) found out that receiver of the information actively monitors the consistency of the information while perceiving the credibility of review.…”
Section: Review Characteristicsmentioning
confidence: 97%
“…Past studies have found strong evidence on the impact of review argument quality (Anastasiei et al 2021;Baharuddin and Yaacob 2020;Thomas et al 2019;Tran and Can 2020;Tsao and Hsieh 2015) and review quality (Bambauer-Sachse and Mangold 2010; Chakraborty and Bhat 2017, 2018b; Chakraborty According to Petty et al (1983), the strength of the argument provided in the message represents the quality of the message. Cheung et al (2009) define argument strength as the quality of the information in the online review.…”
Section: Review Characteristicsmentioning
confidence: 99%
“…In the long run, marketing for the capitalist lifestyle can be instilled in social media users. Not to mention eWOM (electronic-Word of Mouth) that has made the information about a product reach potential buyers easily (Baharuddin & Yaacob, 2020;Rai & Tripathi, 2020). Potential buyers could also access the marketplace through applications conveniently.…”
Section: Social Media Influencers and Lifestylementioning
confidence: 99%